Six-Port-Based Architecture for Phase NoiseMeasurement in the UWB Band - Ávila Ruiz, Juan Manuel; Moscoso Mártir, Álvaro; Durán Valdeiglesias, Elena; Moreno-Pozas, Laureano; De-Oliva-Rubio, José; Molina-Fernández, Íñigo (Hindawi Publishing Corporation, 2014)
A six-port-based frequency discriminator for phase noise measurement is proposed. This circuit makes use of a delay line discriminator configuration, thus not requiring reference oscillator. Furthermore, the use of a six-port network allows an extremely simple and completely passive solution well suited for low power oscillator measurement. A detailed study of the architecture is performed including the system noise sources. Besides, a prototype of the proposed six-port based delay line frequency discriminator is evaluated. Phase noise measurements of a commercial RF VCO are performed and compared with the results obtained with commercial metrology equipment with good agreement.
Keywords: Radiofrecuencia; Phase noise; VCO; Six-port; UWB